Which is the current knowledge on man-made endocrine- disrupting chemicals in follicular fluid? An overview of effects on ovarian function and reproductive health - Shulhai, Anna-Mariia; Bianco, Valentina; Donini, Valentina; Esposito, Susanna; Street, Maria Elisabeth (Frontiers in Endocrinology, 2024)
The increase in female reproductive disorders, such as polycystic ovary syndrome, endometriosis, and diminished ovarian reserve that lead to subfertility and infertility, has encouraged researchers to search and discover their underlying causes and risk factors. One of the crucial factors that may influence the increasing number of reproductive issues is environmental pollution, particularly exposure to man-made endocrine-disrupting chemicals (EDCs). EDCs can interfere with the ovarian microenvironment, impacting not only granulosa cell function but also other surrounding ovarian cells and follicular fluid (FF), which all play essential roles for oocyte development, maturation, and overall reproductive function. FF surrounds developing oocytes within an ovarian follicle and represents a dynamic milieu. EDCs are usually found in biological fluids, and FF is therefore of interest in this respect. This narrative review examines the current knowledge on specific classes of EDCs, including industrial chemicals, pesticides, and plasticizers, and their known effects on hormonal signaling pathways, gene expression, mitochondrial function, oxidative stress induction, and inflammation in FF. We describe the impact of EDCs on the development of reproductive disorders, oocyte quality, menstrual cycle regulation, and their effect on assisted reproductive technique outcomes. The potential transgenerational effects of EDCs on offspring through animal and first-human studies has been considered also. While significant progress has been made, the current understanding of EDCs' effects on ovarian function, particularly in humans, remains limited, underscoring the need for further research to clarify actions and effects of EDCs in the ovary.